(untitled) (Medicine Today, 2019)
Introduction: The aim of the present study was to evaluate the pattern of medication adherence to anti-diabetic drugs among type 2 diabetic patients at two tertiary level hospitals in Mymensingh. Materials and Methods: An observational, cross sectional study was conducted from January 2016 to June 2016 among patients attending at Endocrine Outpatient Department of the Mymensingh Medical College Hospital and Medicine Outpatient Department of the Community Based Medical College Hospital, after obtaining requisite consent from the patients. Once the consultation by the physician was over, the patients were interviewed. Medication adherence was assessed through the specific four questions patient questionnaire, the modified morisky instrument that has high reliability and validity and the patient was considered to be highly adherent if he or she answered in the negative to all four questions (score-0). Results: In a pool of 300 type 2 diabetics, more than half were female (n=223, 74.3%). The mean age of the patients were found to be 50.59 ± 12.57 years. Less than half (37%) of the patients were considered highly adherent, 44% patients were considered moderately adherent and 19% patients were considered poorly adherent to the prescribed anti-diabetic drugs. Conclusion: The participants in the area of study were moderately adherent to their anti-diabetic medications. Measures should be taken to improve patient’s adherence to the prescribed treatment. Medicine Today 2019 Vol.31(1): 19-22